2004
DOI: 10.1016/j.polymer.2004.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic estimation of filler surface energies and correlation with photodegradation of kaolin filled polyethylene

Abstract: Inverse gas chromatography, IGC, has been used to investigate the surface properties of two calcined kaolins and of polyethylene composites containing calcined kaolin. The results reveal differences in the two kaolins that were not found in XPS spectra nor in their influence on the melting behaviour of the polymer. The kaolin that had a markedly higher surface energy and stronger Lewis acid behaviour was found to shower greater photooxidative degradation in accelerated weathering tests. This novel application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…With degradation, the amorphous and interphase fractions in the polymer decrease, resulting in a decrease of elongation at break. Moreover, chain scission in the amorphous phase, leading to reduction in chain length and, thereby, reduces the tendency and possibility of chain slippage and disentanglement, is also responsible for the decrease of elongation at break for aged samples .…”
Section: Resultsmentioning
confidence: 99%
“…With degradation, the amorphous and interphase fractions in the polymer decrease, resulting in a decrease of elongation at break. Moreover, chain scission in the amorphous phase, leading to reduction in chain length and, thereby, reduces the tendency and possibility of chain slippage and disentanglement, is also responsible for the decrease of elongation at break for aged samples .…”
Section: Resultsmentioning
confidence: 99%
“…Specific surface area of the particles is related to the total amount of surface energy available at the start of formation of the solid percolation network. Accordingly this parameter plays an important role, but as soon as adsorption of the polymer chains occurs at the particles surface, this interaction might become the most important variable (Ansari & Price, 2004;Dai & Huang, 1999). Dispersion of the same kaolin powders in paraffin oil and in polybutadiene exemplifies the effect of nature of liquid phase on the corresponding yield stress.…”
Section: Samplementioning
confidence: 99%
“…They found that the alkylammonium cations can provide functional groups that can react with the polymer to improve the strength of the interface between the inorganic component and the macromolecule. Inverse gas chromatography (IGC) has been used to investigate the surface properties of calcined kaolins and the effect on the mechanical properties of a nylon-6 composite containing the clay by Ansari and Price [8,9]. They believed that the modification of the kaolin with an aminosilane coupling agent lowered its surface energy so that it was comparable with that of the polymer matrix and changed the surface from being acidic to being predominantly basic.…”
Section: Introductionmentioning
confidence: 99%